Peran Kelembagaan dalam Sistem Pemasaran Cabai Merah di Sumatera Utara - Nasution, Amelira Haris; Hanter, Hanter; Rahman, Primananda (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2020)
Fluctuation in the price of red chili pepper is an old problem in the horticultural product trade, moreover, the high level of red chili pepper consumption also has an impact on the sensitivity of red chili pepper prices in the market. The cause of this fluctuation is not only due to production and productivity factors of red chili pepper but also due to distribution factors and the role of marketing of each agency. The purpose of this study was (1) to describe the institutions involved in the marketing of red chili pepper; (2) to analyze the functions and roles of institutions in the marketing of red chili pepper; (3) to analyze the potential of institutional development in producing marketing recommendations system in the future. This research was conducted in North Sumatra by selecting 3 districts, namely Karo Regency, Deli Serdang Regency, and Dairi Regency. The data method used was a survey method with qualitative data analysis. The data used consisted of primary data (observation, interviews, and questionnaires) and secondary data (literature study). The method of processing and data analysis used was descriptive qualitative analysis. The results showed: (1) there are 2 main institutions in the marketing of red chili pepper, namely a marketing agency and a farmer institution; (2) those institutions have different roles in the marketing of red chili pepper and the results of the research show that marketing agencies have a bigger role in marketing red chili pepper; (3) the existing STA is the potential for farmer level institutional development. It is necessary to strengthen farmer level institution without forgetting farmers and also marketing institutions that play a role in the red chili marketing system.